Endodontic reintervention in mandibular second molar with c-shape canals and internal root resorption: A case report - Sulastri, Sulastri; Nugroho, Juni J.; Hikmah, Noor; Natsir, Nurhayaty; Trilaksana, Aries C.; Dwiandhany, Wahyuni S. (Hasanuddin University, 2023)
Objective: This case report aims to describe the endodontic reintervention in a mandibular second molar with C-shape canals and IRR.Methods: The tooth had root canal treatment Â± 7 months ago, and there was a history of swelling. Clinical and radiographic examination of tooth #46 showed C-shape root canals configuration, mesial unobturated canal, obturated but not hermetically distal root canal, closed IRR on the mesial and distal roots, and diffuse radiolucency in the periapical.Results: The diagnosis was previously treated with a chronic apical abscess. Endodontic reintervention was performed to eliminate bacteria from the root canal systems, obtain hermetic results in irregular root canals due to closed IRR accompanied by a C-shape configuration, and allow proper healing. The tooth was restored with a zirconia overlay.Conclusion: Endodontic reintervention in mandibular second molar with C-shaped canals and internal root resorption can be successful depending on the choice of treatment plan and procedure.